Psychological coping strategies of student-athletes associated with anterior cruciate ligament injury rehabilitation as perceived by physiotheraphists - Rivera, Karina Ysabel C. 2002-
Sports Psychology uses psychological knowledge and skill to address optimal performance and the overall well-being of athletes. Coping strategies play a crucial role in athletes as it can result in many long-term benefits such as personal performance development. Sports injuries can cause an imbalance and disruption to the lives of athletes as it can potentially result in loss of health and achievement of athletic potential. This study aims to determine the coping process of selected student-athletes recovering from Anterior Cruciate Ligament (ACL) Injury and understand their behaviors through the perspective of their Physiotherapists (PT) as well as understanding how these strategies and behaviors may have affected their recovery process. This qualitative study is designed to compare and analyze the different psychological perspectives of athletes’ coping strategies by conducting semi-structured interviews. The participants are chosen based on a set of criteria as well as the recommendation of the Physiotherapist. Once the interviews are completed, data will be collected and analyzed.